(untitled) (Ustozlar uchun, 2025)
Abstract: Human Resource Management (HRM) plays a crucial role in determining the effectiveness of educational institutions and their ability to maintain academic excellence. However, Human Resource Management practices in many educational settings are often underdeveloped or poorly executed, leading to inefficiencies, lower staff morale, and a decline in overall performance.